Deciphering the Contributions of CRH Receptors in the Brain and Pituitary to Stress-Induced Inhibition of the Reproductive Axis - Raftogianni, Androniki; Roth, Lena C.; García-González, Diego; Bus, Thorsten; Kühne, Claudia; Monyer, Hannah; Spergel, Daniel J.; Deussing, Jan M.; Grinevich, Valery (Frontiers in Molecular Neuroscience, 2018)
Based on pharmacological studies, corticotropin-releasing hormone (CRH) and its receptors play a leading role in the inhibition of the hypothalamic-pituitary-gonadal (HPG) axis during acute stress. To further study the effects of CRH receptor signaling on the HPG axis, we generated and/or employed male mice lacking CRH receptor type 1 (CRHR1) or type 2 (CRHR2) in gonadotropin-releasing hormone neurons, GABAergic neurons, or in all central neurons and glia. The deletion of CRHRs revealed a preserved decrease of plasma luteinizing hormone (LH) in response to either psychophysical or immunological stress. However, under basal conditions, central infusion of CRH into mice lacking CRHR1 in all central neurons and glia, or application of CRH to pituitary cultures from mice lacking CRHR2, failed to suppress LH release, unlike in controls. Our results, taken together with those of the earlier pharmacological studies, suggest that inhibition of the male HPG axis during acute stress is mediated by other factors along with CRH, and that CRH suppresses the HPG axis at the central and pituitary levels via CRHR1 and CRHR2, respectively.